Aquatic Antagonists: Sea Cucumbers (Holothuroidea) - Ellis, Carter R.; Elston, Dirk M.; Joustra, Juan Pedro Lonza; Haddad, Vidal (My University, 2021)
Sea cucumbers are sausage-shaped aquatic creatures living on the ocean floors across the world. They are considered a food delicacy in many countries but also are known to have many beneficial pharmaceutical properties; however, sea cucumbers also contain a dangerous component called holothurin, which has been shown to have a negative impact on the health of both humans and other wildlife. In humans, exposure to holothurin can cause a painful irritant dermatitis, irritation of the mucous membranes, potential blindness, and, if ingested, even possible death. Treatment options include irrigation with seawater, soap, isopropyl alcohol, and vinegar.